2021
DOI: 10.1186/s12969-021-00617-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunological repertoire linked to PSTPIP1-associated myeloid-related inflammatory (PAMI) syndrome

Abstract: Background Mutations along PSTPIP1 gene are associated to two specific conditions, PAPA syndrome and PAMI syndrome, both autoinflammatory disorders associated to disturbances in cytoskeleton formation. Immunological aspects of PAMI syndrome has not yet been reported neither the clinical impact on therapeutical decisions. Methods Clinical data of patients records were retrospectively accessed. Genomic DNA were extracted and sequenced following stand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Our review identified 252 articles through database searches. After eliminating duplicates and excluding unqualified articles, we included 25 relevant articles that described 43 patients with PAMI syndrome [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our review identified 252 articles through database searches. After eliminating duplicates and excluding unqualified articles, we included 25 relevant articles that described 43 patients with PAMI syndrome [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, phenotypic heterogeneity was observed among family members sharing the same variants [ 2 , 3 , 19 , 21 , 29 ]. In most patients, clinical symptoms appeared gradually over a period of several years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, two specific mutations in the same gene and domain (E250 K and E257 K) are associated to a different and specific condition, the PAMI syndrome, what requires caution in genotype versus phenotype correlation. PAPA but not PAMI has a great response to anti-IL1 therapies, and bone marrow transplantation has not yet been reported in PAPA patients [ 13 ]. Moreover, some other nonspecific clinical forms of pyoderma gangrenosum were linked to mutations in other domains of the gene and yet without a clear immunological relation.…”
Section: Discussionmentioning
confidence: 99%